Nanoscale 3D Bioprinting for Osseous Tissue Manufacturing - Wang Y (Dove Medical Press, 2020)
Yujia Wang, 1 Ming Gao, 1 Danquan Wang, 2 Linlin Sun, 1, 3 Thomas J Webster 1, 3 1Department of Chemical Engineering, Northeastern University, Boston, MA 02115, USA; 2Department of Pharmaceutical Sciences, Northeastern University, Boston, MA 02115, USA; 3Wenzhou Institute of Biomaterials and Engineering, Wenzhou Medical University, Wenzhou, Zhejiang 325001, People’s Republic of ChinaCorrespondence: Linlin Sun; Thomas J WebsterDepartment of Chemical Engineering, Northeastern University, Boston, MA 02115, USATel +1 6173732285; +1 6173736585Fax +1 6173736585Email l.sun@neu.edu; th.webster@neu.eduAbstract: 3D printing, as a driving force of innovation over many areas, brings numerous manufacturing methods together from the macro to nano scales. New revolutionary materials (such as polymeric materials and natural biomaterials) can be produced into unique 3D printed nanostructures. The morphology and functionality of various 3D printing methods as well in vitro and in vivo results of their use towards regenerating bone are discussed in this review. This review further focuses nano scale 3D bioprinting technology for bone tissue engineering, mainly including recent progress in research on technical materials and methods, typical applications, and crucial achievements; explaining the scientific and technical challenges for bone tissue fabrication; and describing micro-nano scale 3D printing application prospects, development directions, and trends for the future for this field to realize its full potential.Keywords: orthopedic, nanoparticles, nanotextured, bone, advance manufacturing